2015
DOI: 10.1002/nvsm.1523
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the cultural consumption of a new wave of immigrants: the case of the South Korean community in South West London

Abstract: The purpose of the study was to develop and test a model explaining the cultural consumption of a new immigrant ethnic group (South Korean) in terms of their highbrow, middlebrow, lowbrow, public/private and ethnic minority cultural pursuits. A core premise of the study was that due to the overall higher socio‐economic standing of the South Korean community (in comparison to many other ethnic minority groups residing in the UK), this particular immigrant group would more closely resemble the omnivore and not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The language spoken in a theater, or the genre of music played in a concert may be unfamiliar to immigrants or members of minority groups, limiting their ability to appreciate and enjoy the available cultural supply. Studies in the UK found that individuals from ethnic minorities reported language barriers and difficulty understanding artistic performances (Jermyn and Desai, 2000; Kottasz, 2015). 1…”
Section: Determinants Of Access To Art and Culturementioning
confidence: 99%
“…The language spoken in a theater, or the genre of music played in a concert may be unfamiliar to immigrants or members of minority groups, limiting their ability to appreciate and enjoy the available cultural supply. Studies in the UK found that individuals from ethnic minorities reported language barriers and difficulty understanding artistic performances (Jermyn and Desai, 2000; Kottasz, 2015). 1…”
Section: Determinants Of Access To Art and Culturementioning
confidence: 99%